Dampak Perilaku Merokok di Kalangan Siswa: Studi Kasus pada Salah Satu Madrasah Tsanawiyah Tarbiyah Islamiyah - Putra, Bayu Mandala; Kartika Sari, Widya; Ariani, Winda Ade (Indonesian Journal of Counseling and Development, 2024)
Smoking behavior is one of the negative behaviors exhibited by high school students, with previous studies indicating a high prevalence of this behavior. This study aims to analyze the impact of smoking behavior among students and to identify the efforts made by the school to address student smoking. The researcher employed a qualitative case study approach, involving nine informants: seven students, one homeroom teacher, and one deputy head of student affairs. The research was conducted at one of the Tarbiyah Islamiyah Madrasah in a rural area. Data were collected through interviews, observations, and documentation. The data analysis technique used was the Miles & Huberman interactive model, including a process for checking data validity. The research findings are as follows: (1) The impact of smoking behavior on students is significant in terms of health, with frequent coughing, fatigue, drowsiness during lessons, headaches, sore throats, hoarseness, frequent nausea, and weight loss reported. Academically, smoking behavior leads to decreased concentration and lower academic achievement. (2) Efforts to address this behavior include collaboration between the homeroom teacher and the deputy head of student affairs, who work together to prevent students from leaving the school premises and impose sanctions on smoking students, such as fines, memorization of Qur’an verses, and warning points. If a student accumulates 100 points, they are expelled. This finding underscores the importance of preventive counseling services in schools. Counselors can design a smoking behavior prevention program that includes regular counseling on the negative impacts of smoking on health, academics, and social life.